THE NOVELTY OF PLOT IN LEILA S CHUDORI'S PULANG - Viona Gita Kusaeri (Saksama: Jurnal Sastra, 2022)
Literary works are built from the harmony of intrinsic elements such as theme, plot, characterization, setting, point of view, style, and mandate. Plot is one of the crucial elements in a story which can combine all the elements in a story to become harmonious. From the plot, we can know the events of the character’s characteristics and the conflicts faced by the story. It can clearly describe the storyline that wants to create by the writer. Pulang by Leila S Chudori is one of the novels that have a unique plot which is created from the letter’s media. The new way of conveying the plot is called novelty.  The novelty is created for avoiding monotony in a story. Every stage of plot such as exposition, inciting moment, rising action, conflict/climax, falling action and denonement can be made to make a surprise so that the reader feels interested and curious about the next stage of plot. This is what Leila does to build her plot more interesting and unique. Leila in Pulang uses a regressive plot because the sequence of events told in fiction is not chronological, the story starts from the middle stage when Dimas Suryo is already in Paris. Besides the letter media that Leila uses in the story, she also used novelty for the renewal of the written media based on the developments of electronic media from 1965-1998. Through this kind of novelty, Leila succeeds in getting the reader to be influenced by Indonesia’s dark history which is written from a different perspective.